Pengaruh Financing to Deposit Ratio, Capital Adequacy Ratio dan Non Performing Financing terhadap Profitabilitas pada Bank Umum Syariah - Muhammad Rivandi; Tania Gusmariza (Politeknik Ganesha Medan, 2021)
Probability is the ability of a Company to generate profits for a certain period. Profitability shows the ratio of profit to assets or capital that creates profit. Bank Indonesia prioritizes the profitability of a bank which is measured by assets whose funds mostly come from public savings funds so that ROA is considered more representative in measuring banking profitability. This study aims to examine The effect of the Financing to Deposit ratio, Capital Adequacy Ratio, and Non-Performing Financing on profitability. The population of this study is all Islamic commercial banking companies in Indonesia from 2017 to 2019, with the selection of a sample of companies using purposive sampling, so that the number of samples that match the criteria are eleven companies. The data analysis method used in this study is a panel regression model. Based on the results of hypothesis testing, that the Financing to Deposit Ratio and Non-Performing Financing has no effect on profitability, while the Capital Adequacy Ratio has a positive and significant effect on profitability.